Estudo bioeletroquímico de compostos eletrobioativos - relação estrutura-eletroatividade e utilização de biossensor de DNA no estudo de agentes intercalantes e alquilantes de DNA - Paula, Francine Santos de (2018)
Electrochemical methods are very useful in Medicinal Chemistry and play important roles in the elucidation of the mechanism of biological action and also on the establishment of structure-electrochemical activity relationship. In the present work, we performed studies in the correlation of structure-redox potential and applied DNA biosensor in the investigation of the interaction of different substances towards DNA. Arylazoxy compounds were studied by cyclic voltammetry, in protic (aqueous / ethanolic phosphate buffer, pH 6.9) and aprotic (DMF + TBAP 0.1 mol L-1) media. In both media, linear relationships between EpIc (potential of first cathodic wave), Eredox (for aprotic) and Hammett substituent constants (σp, σ -) were observed. The reduction potentials correlate considerably better with (σp, σ -), showing the strong influence of resonance factors in the mechanism of reduction. The effect of pH on the reduction of calvatic acid and similar 2, a nonsubstituted compound, in aqueous ethanolic solution (20% v:v), was studied through differential pulse voltammetry. The Ep and Ip vs. pH plots showed distinct regions. The apparent pKa values of 3.3 and 7.9 for calvatic acid and 6.21 for the unsubstituted one were obtained and were similar to the reported ones. A double-stranded calf thymus DNA-Glassy Carbon (dsDNA-GC) biosensor was used as a model to study the possible DNA-damaging abilities of calvatic acid, berenil and mechlorethamine towards dsDNA, in situ at a charged interface. Concerning this dsDNA-GC biosensor, two ways were used for performing the experiments – one with the analytes in solution and the other with them incubated into the dsDNA gel, immobilized directly on the electrode. Calvatic acid does not damage dsDNA. Any diagnostic peak related to the oxidation of bases was observed. It concentrates in the dsDNA matrix. The DNA damaging abilities of berenil were shown. DPV-detectable DNA damage, with berenil incubated into the dsDNA gel, could be observed at concentrations of 1 as low as 1 x 10-5 mol dm-3. When berenil was applied to the dsDNA-GC biosensor in buffer solution, the method was much less sensitive and DPV-detectable DNA damage could be detected only at concentrations of 1 of 1 x 10-3 mol dm-3. This interaction was shown to be time dependent and the process was slow. ssDNA in solution, on a glassy carbon electrode was used for the analysis of the interaction of berenil, with evidence of selective interaction with adenine. Electrochemical voltammetric in situ sensing of dsDNA damage caused by mechlorethamine, incubated into the dsDNA gel, after 24 hours contact, was possible by the appearance, in the differential pulse voltammograms, of the diagnostic peaks of the nucleobases guanine and adenine oxidation that indicate interaction and damage to DNA. The effect of concentration of mechlorethamine and its time of exposition in solution, in the presence of dsDNA-GC are also reported. With three hours of exposition, the guanine oxidation peak is already visible and concentration of mechlorethamine in the order of 10-5 mol L-1 leads to clearly discernible diagnostic signals. From a qualitative viewpoint, preparation of the biosensor and incorporation of dsDNA gel and substrate with a contact time of 24 h would be the method of choice for the observation of interactions between berenil and DNA, and detection of consequential oxidative damage. As the dsDNA biosensor is easily prepared and gives results for DNA damage in a reasonable time, they could be used as an analytical device to investigate potential new drugs targeting DNA.